Perencanaan Sistem Penyediaan Air Bersih di Desa Leilem Dua Kecamatan Sonder Kabupaten Minahasa - Ratu, Yosua Aditya; Mananoma, Tiny; Wallah, Steenie Edward (Edutik : Jurnal Pendidikan Teknologi Informasi dan Komunikasi, 2025)
ABSTRAK Air adalah elemen vital yang menjadi sumber kehidupan utama. Dari hasil proyeksi yang didapat jumlah jiwa desa Leilem Dua selama 15 tahun berjumlah 441 jiwa. Dari hasil analisis yang dilakukan untuk kebutuhan air di desa Leilem Dua, kebutuhan domestik bertotal 0.205 l/det dan total kebutuhan air non domestik 0.031 l/det sehingga untuk total kebutuhan di desa Leilem Dua berdasarkan perencanaan berjumlah 0.235 l/det. Analisis menggunakan perangkat lunak EPANET dibagi dalam dua bagian yaitu jaringan transmisi dan juga jaringan distribusi. Dari hasil analisis yang dilakukan menggunakan perangkat lunak EPANET, untuk jaringan transmisi, kecepatan pada pipa bernilai 0,36 m/det dan tekanan pada ujung pipa bernilai 25,37 m dan menggunakan pipa HDPE 2 inch. Dari hasil analisis untuk pipa distribusi didapat tekanan pada ujung pipa node 10 = 14,62 m, node 9 = 20,64, node 8 = 17,49 dan node 13 = 27,75 dengan panjang pipa yang didapat, pipa 3 inch sepanjang 150 m, pipa 2 inch sepanajang 850 m, pipa 1,5 inch sepanjang 220 m dan pipa 1 inch sepanajang 250 m. Untuk kecepatan yang ada pada pipa memenuhi kriteria peraturan mentri pekerjaan umum nomor: 18/PRT/M/2007. ABSTRACT Water is a vital element and the primary source of life. Based on the projections, the population of Leilem Dua village over the next 15 years is estimated to be 441 individuals. From the analysis conducted regarding water needs in Leilem Dua, the total domestic water demand amounts to 0.205 Liters per second, while the non-domestic water demand totals 0.031 Liters per second. Therefore, the overall planned water requirement for Leilem Dua village is 0.235 Liters per second. The analysis using EPANET software is divided into two parts: the transmission network and the distribution network. The results of the analysis for the transmission network indicate that the velocity in the pipe is 0.36 meters per second, and the pressure at the end of the pipe is 25.37 meters, using a 2-inch HDPE pipe. For the distribution network, the pressure at the end of the pipes is as follows: node 10 = 14.62 meters, node 9 = 20.64 meters, node 8 = 17.49 meters, and node 13 = 27.75 meters. The pipe lengths used are: 150 meters of 3-inch pipe, 850 meters of 2-inch pipe, 220 meters of 1.5-inch pipe, and 250 meters of 1-inch pipe. The velocity in the pipes meets the criteria set by the Minister of Public Works Regulation No. 18/PRT/M/2007.